Muscle Spindles in the Levator Palpebrae Superioris Muscle of Human Adults. Issue 4 (June 2021) - Takahashi, Yasuhiro; Ohmichi, Yusuke; Lee, Patricia Ann L.; Naito, Munekazu; Nakano, Takashi; Kakizaki, Hirohiko
Abstract : Abstract: In this experimental anatomic study, the authors examined the number and distribution of muscle spindles in the levator palpebrae superioris (LPS) muscle of human adults. This study included 11 orbits from 11 cadavers (mean age at death, 81.9 years). The LPS muscles were harvested and equally divided into 5 sections using transverse incisions. Muscle spindles were counted in each section. Consequently, muscle spindles were identified in 4 (36.4%) of the 11 orbits studied. One to 4 muscle spindles were identified in each of these 4 orbits. All muscle spindles were found in the most proximal section (the muscle origin), and no muscle spindles were identified in the other sections. The results indicate that the LPS muscle is associated with a smaller number of muscle spindles as compared with the rest of the extraocular muscles. Since higher muscle spindle numbers are associated with finer motor movements, eyelid opening does not seem to require much precision, compared to ocular movement.